Silicone rubber matrix composites with shear thickening fluid microcapsules realizing intelligent adaptation to impact loadings. (December 2022) - Zhu, J.Q.; Gu, Z.P.; Liu, Z.P.; Zhong, F.C.; Wu, X.Q.; Huang, C.G.
Abstract: In this paper, silicone rubber matrix composites with shear thickening fluid microcapsules (SR-STF) with intelligent adaptation to impact loadings are fabricated for advanced impact protective structure. The composites exhibit more flexibility at low strain rates but higher stiffness at high loading rates, indicating significant strain-rate sensitivity. In addition, the initial flexibility and the strain-rate sensitivity of the composite increase with increasing the mass fraction of the STF microcapsules, which should be ascribed to the shear thickening and compressive jamming of the STF microcapsules in the composite during impulse loadings. Based on experimental results, a hyper-viscoelastic constitutive model is developed, in which the influence of the mass fraction of STF microcapsules, the strain-rate sensitivity, and the strain-hardening effect are taken into account. The paper develops a practical strategy for applications of STF in soft protective structures and provides a reliable prediction of the dynamic mechanical behavior of the SR-STF composites. Graphical abstract: Image 1 Highlights: Spherical STF microcapsules are successfully dispersed evenly and sealed firmly in the silicon rubber matrix. The mechanical behavior of the SR-STF composites under various strain rates is measured. SR-STR composites show smart adaptation to various loading rates by changing flexibility at different loading conditions. A constitutive model considering effects of strain hardening, strain-rate strengthening, and content of STF is developed. A critical strain rate, above which the influence of STF on the strength of the composite reverses, is predicted.